Optimalisasi Pembelajaran Inovatif Berbasis Deep Learning bagi Guru Sekolah Dasar di Kecamatan Tarik, Sidoarjo - Via Yustitia; Danang Prastyo; Achmad Fanani; Apri Irianto; Anis Rahmawati; Dinda Maharani Verdikasari (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to optimize the understanding and skills of elementary school (SD) teachers in Tarik District in implementing innovative learning based on deep learning. The concept of deep learning in the context of education does not solely refer to the use of technology, but also includes a deep, reflective, and meaningful learning approach. Through this approach, teachers are expected to be able to create a learning environment that encourages students to think critically, creatively, and be able to collaborate effectively. This activity was attended by 34 elementary school teachers from eight schools in the Tarik District area. In addition to providing training related to deep learning concepts and strategies, such as project-based learning and problem-based learning, this activity also introduced the use of OLabs (Online Labs), which is a virtual laboratory platform that can be accessed for free and is specifically designed to support the implementation of online experimental learning. The use of OLabs provides an efficient and flexible alternative, especially for educational units that have limited laboratory facilities. Based on the results of the evaluation, there was a significant increase in teachers' understanding of innovative learning principles, as well as a commitment to implement the approach in an adaptive manner and in accordance with the context of each school. This activity is expected to be the starting point in efforts to strengthen the pedagogic capacity of teachers, in order to support the implementation of the Independent Curriculum and answer the challenges of 21st century education.